Pakaian sebagai sumber inspirasi lukisan - Harun (FSP ISI Yogyakarta, 2014)
Clothing is an identity and cultural heritage is very important and should be in the preserve. Indonesia is a country rich in culture and ethnicity, reflected on clothing to identify one with the other tribes. By preserving the cultural heritage, the younger generation will not lose the ancestral cultural identity that has been passed down through generations. Not only as a reflection of one's personal self, clothing is also a reflection of human identity are communal. As a marker of the existence of a set of ethics and human communities. However, through clothing is also a process of discrimination and hegemony lasted. Since the colonial era, independence until now the process of discrimination and hegemony through clothing still occur. Moreover, in this era of modernization now be following the clothes worn are vibrant fashion in western countries. By forgetting the essence and function of clothing, people began consumptive use by choosing clothes that are popular in western countries, and chose to leave the traditional clothing that is considered outdated.